LWEDM: Learning with error based secure mobile digital rights management system. Issue 2 (20th December 2020) - Dharminder, Dharminder
Abstract: Mobile multimedia security is essential to ensure a secure communication in industries, businesses, and organizations. Mobile multimedia is a new concept for an enterprise, where organizations need to be secure. In the last decade, a number of anonymous authentication protocols have been designed based on factorization and discrete logarithm assumptions. Shor's algorithm solves a number‐theoretic assumption in polynomial time using postquantum computers that creates a trouble. However, learning with errors is an advanced hard assumption that cannot be solved by any known existing quantum algorithm. This inspires one to design an anonymous postquantum authentication protocol for the mobile digital rights management system. The protocol has been proved secure in a random oracle model under learning with errors assumption. Moreover, the article contributes an informal security discussion, an implementation using automated validation of internet security protocols and applications. The performance analysis ensures its efficiency even in the postquantum era. Abstract : 1) Post‐Quantum secure digital rights management system. 2) Post‐ Quantum secure key agreement in a digital rights management system. 3) Post‐Quantum anonymous authentication protocol.